2023
DOI: 10.1039/d3gc00864a
|View full text |Cite
|
Sign up to set email alerts
|

Multiple promotion effect of mixed solvents on the oxidative degradation of thermosetting polymers

Abstract: Mixed solvents significantly promote oxidative degradation of thermosets without heat input by improving mass transfer via promoting resin swelling while improving oxidation activity of oxidizer through coordination of organic solvent with metal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…As a result, it was difficult to recover by precipitation by poor solvents. The degradation products are linear oligomers of epoxy resins, , and the differences in the NMR spectra for the degradation products of different amine-cured epoxy resins are mainly attributed to the curing agent part (Figure S4). Elemental analysis showed an increase in the contents of N and O after degradation (Figure S5), while two new peaks attributed to nitro appeared in the infrared spectra at 1343 and 1539 cm –1 for the degradation products (Figure S2b), suggesting that oxidation and nitrification occurred in the degradation process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, it was difficult to recover by precipitation by poor solvents. The degradation products are linear oligomers of epoxy resins, , and the differences in the NMR spectra for the degradation products of different amine-cured epoxy resins are mainly attributed to the curing agent part (Figure S4). Elemental analysis showed an increase in the contents of N and O after degradation (Figure S5), while two new peaks attributed to nitro appeared in the infrared spectra at 1343 and 1539 cm –1 for the degradation products (Figure S2b), suggesting that oxidation and nitrification occurred in the degradation process.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work, cerium ammonium nitrate (CAN) aqueous solution was successfully used to degrade amine-cured epoxy thermosets. 23 Recently, we observed that the introduction of CH 3 CN can significantly improve the degradation rate by facilitating diffusion and improving the oxidation activity of oxidizer salt, 24 which made the process promising in industrial applications. Moreover, this increases the differences in degradation behaviors among the thermosets, making it possible to evaluate the effect of amine curing agents.…”
Section: ■ Introductionmentioning
confidence: 99%